Peripheral Slits Microstrip Antenna Using Log Periodic Technique for Digital Television Broadcasting - Indra Surjati; Yuli Kurnia Ningsih; Syah Alam (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper proposed a new design of log periodic microstrip antenna using peripheral slits for Digital Video Broadcasting applications in DKI Jakarta. Applying peripheral slits can be reduced the dimension of antenna up to 62.6% with its dimension 400 mm x 150 mm using 4 patches in different frequencies. The patches are one another connected using log periodic technique. The measurement results showed that the antenna was operating at frequency ranges of 450 MHz to800 MHz with impedance bandwidth of 350 MHz,VSWR ≤ 2 and return loss ≤ -10dB. The proposed antenna could receive 11 DVB stations with high definition quality pictureand only channel number 24, such as RCTI, Global TV and MNC TV can not reveive signals as expected.